Напрями професійного розвитку майбутнього вчителя фізичної культури - Драгнєв, Юрій (Видавництво Львівської політехніки, 2012)
Рассматриваются векторы профессионального развития будущего учителя физической культуры в высшем физкультурном образовании. Доказывается, что деятельность в условиях информационно-образовательного пространства становится все более инновационной, что разрешает иметь личный вектор профессионального развития в информационном обществе. The article considers vectors of professional development of the future teacher of physical culture in the higher sports education. It proves that the activity in conditions of informational and educational space becomes more and more innovative, which enables the existence of a personal vector of professional development in the informational society.
Направления профессионального развития будущего учителя физической культуры
Directions of professional development of future teacher of physical culture
Keywords: векторы профессионального развития; высшее физкультурное образование; будущие учителя физической культуры; vectors of professional development; higher sports education; future teachers of physical culture